The influence of school-based musical training on acculturation processes in children: Findings from a longitudinal study. (March 2023) - Francisca Lupu, Stefana; Roden, Ingo; Krone, Mara; Chantah, Jasmin; Frankenberg, Emily; Bongard, Stephan; Kreutz, Gunter
Previous work suggests that musical training can enhance acculturation processes. This study examined this assumption among third-graders with migrant backgrounds within a longitudinal framework. A total of 54 children (31 females; 23 males; mean age: 8.85 years) were assigned to one of three groups in a quasi-randomized procedure: (a) music training (singing or instrumental), (b) game-based mathematical training (board and card games), and (c) controls (do-nothing). We assumed that the music children showed increases in host culture orientation, perceived school integration, and in their individual self-concept in comparison to their peers with alternative or without additional training. Music children received weekly 45 min sessions over a period of 10 months. Data were collected at baseline, after one school year, and at a follow-up about six months after intervention. Results showed no advantages for music children across dependent measures. Increases of perceived school integration and self-concept were significant across groups. In sum, our results failed to replicate the main findings from previous studies. They suggest that weekly musical training over a period of 10 months might not be sufficient to improve the acculturation process or to enhance the self-concept of primary school children with a migration background.